Leitura e narração de histórias por pais de crianças de 2 a 5 anos - Fontes, Luciane Mees [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The period between birth and 6 years of age has been considered as extremely important for the development of aspects that will influence throughout the life of the individual. Some activities, of low financial and logistic cost, have been very effective to aid in the stimulation of language and cognitive aspects in childhood. Among them, storytelling. This work aims to investigate the conceptions and stimulate the reading and narration of stories by parents of children from 2 to 5 years, considering that parents and guardians play a mediating role in the formation of readers. Participants of the study were 8 relatives of children aged 2 to 5 years attending a municipal school. The study consisted of two parts, in the first, the participant answered a questionnaire about the habits of telling stories to their children; then four workshops were held to encourage reflection on storytelling, repertoire, and the impact of activity on children's development, and workshops included storytelling, book-making and guidance on reading stimuli. The data collection was performed through a questionnaire applied before and after the meetings. The data were systematized through a qualitative approach, in order to analyze the repertoire of parents and guardians, as well as to evaluate the performance after the meetings. The results indicated that the practice of reading activity was poorly performed and / or little used before the meetings, in addition, that the holding of discussion and reflection meetings on child stimulation through storytelling for parents increases the repertoire and the knowledge about the subject, besides the verbal report of change in the quantity and quality of narration activities with children. It is suggested that more studies explore possibilities for reflection and operationalization of storytelling activities for parents and family and to seek the impact of these activities on child development.

O período entre o nascimento e os 6 anos de idade vem sendo apontado como de extrema importância para o desenvolvimento de aspectos que influirão ao longo de toda a vida do indivíduo. Algumas atividades, de baixo custo financeiro e logístico, tem se mostrado muito efetivas para auxiliar na estimulação linguística e de aspectos cognitivos na infância. Entre elas, a narração de histórias. Esse trabalho tem por objetivo investigar as concepções e estimular a leitura e narração de histórias por pais de crianças de 2 a 5 anos, considerando que os pais e responsáveis desempenham papel mediador na formação de leitores. Participaram do estudo, 8 familiares de crianças de 2 a 5 anos, frequentadoras de uma escola municipal. O estudo constou de duas partes, na primeira, o participante respondia um questionário sobre os hábitos de contar histórias para seus filhos; então foram realizadas quatro oficinas nas quais se fomentava a reflexão sobre o ato de contar histórias, o repertório e o impacto da atividade no desenvolvimento infantil, assim, as oficinas incluíam atividades de narração, confecção de livros e orientações a respeito dos estímulos a leitura. A coleta de dados realizou-se por meio de um questionário aplicado antes e após os encontros. Os dados foram sistematizados mediante abordagem qualitativa, no intuito de analisar o repertório dos pais e responsáveis, bem como avaliar o desempenho após os encontros. Os resultados obtidos indicaram que a prática da atividade leitura era pouco realizada e/ou pouco aproveitada antes dos encontros, além disso, que a realização de encontros de discussão e reflexão sobre a estimulação infantil por meio da narração de histórias para pais aumenta o repertório e o conhecimento acerca do tema, além do relato verbal de mudança na quantidade e qualidade das atividades de narração com as crianças... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Leitura; Historias; Pais